Addressing the Levels of Knowledge and Awareness on Human Rights and the Right to Food in a Group of Students at the University of Jordan - Al-Domi, Hayder (Pakistan Journal of Nutrition, 2011)
An international organization of human rights is continuously building, improving and implementing the goals of the basic HRs emphasizing more on the right to adequate food and the right to be free from hunger through the resolutions adopted by the General Assembly. The aim of this study was to explore the knowledge and awareness to the Right to Food (RTF) and selected Human Rights (HRs) among a group of students at the University of Jordan, Jordan. One thousand one hundred five graduands (39% males and 61% females) from different faculties of the University were interviewed. Issues on the RTF and basic HR were collected and a questionnaire was developed. More than a half of all graduands demonstrated a moderate level of awareness to the studied human rights. However, a high level of knowledge and awareness to the right to food as basic HR was observed, approximately the same in both genders females (79.8%) and males (77.7%). Awareness to right to food as essential right was considered satisfactory in graduands of medical (81.6%), Scientific (80.5%), Agriculture (81.5%) and Graduate Studies (82.1%), but was unsatisfactory in the graduands of the humanitarian faculty (68.5%). It is therefore concluded that participants in this study demonstrated a satisfactory level of knowledge and awareness on HRs, whereas, there were great concerns regarding the lack of awareness on the RTF as a basic HR. This could hinder the implementation and realization of the right to adequate food and the right to be free from hunger in the context of national food security. This is an important area for policy makers to building the capacity of people in order to support the realization of the RTF at all national levels.